1995
DOI: 10.1136/bmj.310.6986.1037
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of acute symptomatic toxoplasma retinochoroiditis in south London according to country of birth

Abstract: A substantial proportion of people with acute symptomatic toxoplasma retinochoroiditis were born outside the country, and the number born in Britain was smaller than the number previously estimated to develop retinochoroidal lesions due to congenital toxoplasmosis. These findings suggest that prenatal screening for toxoplasmosis in Britain may be of limited benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 32 publications
3
15
1
1
Order By: Relevance
“…Compared to other countries, our CTox rate at one year of age was similar to that found in Poland (1.1/1,000) (Paul et al 2001) and was greater than those reported for Sweden (0.07/1,000) (Evengard et al 2001), Massachusetts, USA (0.08/1000) (Guerina et al 1994) and London, England (0.08/1,000) (Gilbert et al 1995), Switzerland (0.12/1,000) (Signorell et al 2006), Barcelona, Spain (0.3/1,000) (Munoz Batet et al 2004) and Denmark (0.4/1,000) . Only in Paris, France was a higher occurrence reported (1.9-3.2/1,000) (Remington et al 2005).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Compared to other countries, our CTox rate at one year of age was similar to that found in Poland (1.1/1,000) (Paul et al 2001) and was greater than those reported for Sweden (0.07/1,000) (Evengard et al 2001), Massachusetts, USA (0.08/1000) (Guerina et al 1994) and London, England (0.08/1,000) (Gilbert et al 1995), Switzerland (0.12/1,000) (Signorell et al 2006), Barcelona, Spain (0.3/1,000) (Munoz Batet et al 2004) and Denmark (0.4/1,000) . Only in Paris, France was a higher occurrence reported (1.9-3.2/1,000) (Remington et al 2005).…”
Section: Discussionmentioning
confidence: 63%
“…The occurrence of congenital toxoplasmosis (CTox) was found to be 0.07/1,000 births in Sweden (Evengard et al 2001), 0.08/1,000 in Massachusetts, USA, and in London, England (Guerina et al 1994, Gilbert et al 1995, 0.12/1,000 in Switzerland (Signorell et al 2006), 0.3/1,000 in Barcelona, Spain (Munoz Batet et al 2004), 0.4/1,000 in Denmark ), 1.1/1,000 in Poland (Paul et al 2001), and 1.9-3.2/1,000 in Paris, France (Remington et al 2005).…”
mentioning
confidence: 99%
“…In particular, several studies have shown higher incidences and severities of chorioretinitis in Brazil (146) or Colombia, both during primary infections of immunocompetent subjects and in congenitally infected infants. The strain genotype could also be an explanation for the high proportion of retinochoroiditis (19 of 100 cases with proven acute infection) in an outbreak in Victoria, British Columbia, Canada, where an atypical cougar isolate was suspected to be the cause (40), and for the 100-fold-higher incidence of ocular toxoplasmosis in patients born in Africa than in patients born in Britain (148). Moreover, in the British Columbia outbreak, 20% of patients had recurrent episodes of retinochoroiditis (47).…”
Section: Toxoplasmosis In Immunocompetent Subjectsmentioning
confidence: 99%
“…The vast majority of these women were treated during pregnancy, and the vast majority of the infected children were also treated. According to the 2006 EUROTOXO study report, 9 reported rates of CT vary across different European countries (ie, 0.7 in 10 000 in Sweden, 92 0.8 in 10 000 in the United Kingdom, 113 1 in 10 000 in Austria, 3 1.6 in 10 000 in Denmark, 114 5 in 10 000 in Switzerland, 11 in 10 000 in Poland, 115 and 13 in 10 000 in Germany 9 ). However, the differences in those rates should be interpreted cautiously because of chronologic and methodologic differences.…”
Section: Figurementioning
confidence: 99%